2003
DOI: 10.1021/bp025721b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study on the Enzymatic Resolution of Homophenylalanine Ester Using Ionic Liquids

Abstract: Two ionic liquids (ILs) were investigated as novel media for the enzymatic resolution of amino acid ester to obtain enantiomeric amino acid homophenylalanine. The effects of solvent nature, polarity, and concentration on the kinetic resolution were investigated. With change in solvent concentration, a systematic study shows that an improved enzyme activity can be obtained by adjusting these solvent parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 10 publications
0
27
0
1
Order By: Relevance
“…[16][17][18][19] AAILs have been employed as chiral solvents or reactants for dissolution and stabilization of cellulose, nucleic acids, carbohydrates and other species of primary biological importance. [20][21][22][23][24][25] On the theoretical front, molecular dynamics (MD) simulations on the ILs composed of deprotonated amino acid anions and choline cation revealed that their formation is facilitated through proton transfer involving the hydrogen bond effectively neutralizing cation and anion. 26 Fileti and coworkers 27 A molecular level understanding of noncovalent interactions encompassing hydrogen bonding, steric repulsion, aromatic ring stacking and electrostatic interactions should prove useful 5 for designing of task specific ILs.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] AAILs have been employed as chiral solvents or reactants for dissolution and stabilization of cellulose, nucleic acids, carbohydrates and other species of primary biological importance. [20][21][22][23][24][25] On the theoretical front, molecular dynamics (MD) simulations on the ILs composed of deprotonated amino acid anions and choline cation revealed that their formation is facilitated through proton transfer involving the hydrogen bond effectively neutralizing cation and anion. 26 Fileti and coworkers 27 A molecular level understanding of noncovalent interactions encompassing hydrogen bonding, steric repulsion, aromatic ring stacking and electrostatic interactions should prove useful 5 for designing of task specific ILs.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic resolution of amino acids is influenced by solvent nature, polarity, and concentration. 17 It was observed that improved enzyme activity could be obtained by adjusting these solvent parameters. A systematic study with variation in ionic liquid concentration in the reaction mixture showed that best results in terms of enantiomeric excess and product yields are obtained with 15% ionic liquid solution in water.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 A report in the literature showed that organic solvents have significant effect on the activity and enantioselectivity of protease in hydrolyzing esters or peptides. 4 However, based on our earlier successful studies in ionic liquids 17,18 and with the foreseeable advantages and goal of finding an environmentally friendly, i.e., ''green'' medium to substitute organic solvents, we investigated the resolution of a series of amino acid esters using porcine pancreas lipase (PPL). In this article, we report the results of this study.…”
mentioning
confidence: 99%
“…The solvent optimization done with N-acetyl-DL-homophenylalanine ethyl ester 1 (Fig. (1 [21]. When the reaction was studied in acetonitrile, lower ee values were observed at higher concentrations of acetonitrile mainly because of the inhibition of the enzyme activity by acetonitrile.…”
Section: Enzyme Mediated Enantioselective Reactions In Ionic Liquidsmentioning
confidence: 99%